APPLICATION OF INFORMATION AND COMMUNICATION TECHNOLOGY (ICTS) IN THE EFFECTIVE TEACHING AND LEARNING OF HOME ECONOMICS IN SECONDARY SCHOOLS IN NIGERIA - Uwameiye, B.E. (European Scientific Journal, ESJ, 2015)
Home Economics is one of the pre vocational subjects that has faced s everal criticisms since it’s introduction into the Nigeria National School Curri culum, among the criticisms is the method adopted by the teachers.This paper therefore examines the need to apply Information and Communication Techn ology in the effective teaching and learning of Home Economics in Secondar y Schools in Nigeria. It reviewed the concept of ICT, and its place in teaching and learning. ICT tools that are suitable for use in the three areas of Home Ec onomics were identified.The tools were radio, television, cameras, video and computers others were social networks such as emails and search engines. Th e benefit of using ICT and factors militating against the effective use of ICT were highlighted. One of the suggestions on ways of solving the problems of using ICT among teachers in this paper is that training of teachers for Home Economics should include basic ICT and computer mastery.